Climate-Smart Cocoa in Ghana: How Ecological Modernisation Discourse Risks Side-Lining Cocoa Smallholders - Nasser, Felix; Maguire-Rajpaul, Victoria A.; Dumenu, William K.; Wong, Grace Y. (Frontiers in Sustainable Food Systems, 2020)
Climate-smart agriculture (CSA) aims to transform and reorient farming systems to decrease greenhouse gas emissions, boost adaptive capacity, and improve productivity while supporting incomes and, ostensibly, food security. In Ghana—the world's second biggest cocoa producer—the cocoa sector is challenged by increasing global cocoa demand, climate change impacts, as well as mounting consumer pressure over cocoa's deforestation. Climate-smart cocoa (CSC) has emerged to address these challenges as well as to improve smallholder incomes. As with CSA more widely, there are concerns that CSC discourses will override the interests of cocoa smallholders, and lead to inequitable outcomes. To better understand if and how the implementation of CSC in Ghana can meet its lofty ambitions, we examine (1) the dominant CSC discourses as perceived by stakeholders, and their reflection in policy and practice, and (2) subsequent implications for cocoa smallholders through an equity lens. Through semi-structured interviews and focus group discussions with key stakeholders in Ghana's cocoa sector, we find overwhelming consensus for an ecological modernisation discourse with the promise of a “triple win” narrative that simultaneously stops deforestation, supports climate mitigation and adaptation, and increases smallholder livelihoods. Moreover, we find that implementing CSC on the ground has generally converged around “sustainable intensification” and private-sector-led partnerships that aspire to generate a “win-win” for environment and productivity objectives, but potentially at the expense of delivering equitable outcomes that serve smallholders' interests. We find that the success of CSC and the overly-simplistic sustainable intensification narrative is constrained by the lack of clear tree tenure rights, complexities around optimal shade trees levels, potential rebound effects regarding deforestation, and the risks of agrochemical-dependence. More positively, local governance mechanisms such as Ghana's Community Resource Management Area Mechanisms (CREMAs) may give cocoa smallholders a stronger voice to shape policy. However, we caution that the discursive power of dominant private sector actors may risk side-lining equity which could prove detrimental to the long-term wellbeing of Ghana's ~800,000 cocoa smallholders.